The Spectrum of Children's Palliative Care Needs: a classification framework for children with life-limiting or life-threatening conditions. Issue 3 (4th March 2014) - Shaw, Karen L; Brook, Lynda; Mpundu-Kaambwa, Christine; Harris, Nicky; Lapwood, Susie; Randall, Duncan
Abstract : Objectives: This paper examined the potential of a new classification framework, The Spectrum of Children's Palliative Care Needs, to facilitate identification of children with palliative care needs for the purposes of minimum data set collection and population needs assessment. Methods: Health and social care professionals (n=50) in a range of paediatric palliative care settings applied The Spectrum to (i) clinical vignettes and (ii) consecutive children on their caseloads. They also provided confidence ratings and written comments about their experiences. Inter-rater reliability, conceptual validity, acceptability, feasibility and sustainability were examined. A subset of professionals (n=9) also participated in semistructured telephone interviews to provide further insight. Results: Inter-rater reliability for the vignettes (κ=0.255) was fair. However, professionals were more confident applying The Spectrum to their caseloads, which included children (n=74) with a range of life-limiting/life-threatening conditions. The Spectrum made conceptual sense in relation to these children and was considered to offer a meaningful way to define the eligible population in service mapping. Benefits for clinical work (eg, facilitating patient review, workload management, clinical audit) and research were also identified. However, important threats to reliability were highlighted. Conclusions: Preliminary assessment of The Spectrum confirms its potential to promote consistent data set collection in children's palliative care. The results have been used to produce a revised version and user guidelines to address issues raised by participants. However, further research is required to further validate the framework and establish its relevance to families' self-defined needs.